2015
DOI: 10.1039/c5ra12192b
|View full text |Cite
|
Sign up to set email alerts
|

Improving interfacial electron transfer and light harvesting in dye-sensitized solar cells by using Ag nanowire/TiO2 nanoparticle composite films

Abstract: a Metallic Ag nanowires coated by TiO2 nanolayer (AgNWs@TiO2) were employed as electron conductor in the mesoporous photoanodes (developed by TiO2 nanoparticles, P25) of dye-sensitized solar cells (DSSCs). Our results demonstrate that the AgNWs@TiO2 (in an optimized content of 3 wt% in photoanode) improved the energy conversion efficiency (η) of the DSSC from 4.68 to 5.31% compared to the DSSC without AgNWs@TiO2 (pure P25). Such improvement could be mainly attributed to the reduced TiO2/dye/electrolyte interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…(2) In any case, where thermal treatment is involved in the fabrication process, noble metal nanostructures are likely to lose their optical properties due to deformation, agglomeration, or Ostwald ripening. For example, high-temperature annealing (∼500 °C) is necessary to fabricate DSSCs, and plasmonic metal nanostructures coated with SiO 2 or TiO 2 layers kept their shape after the annealing process, indicating that protective layers can provide thermal and structural stability. , (3) In conventional DSSCs where iodine-based liquid redox couple is used, rapid corrosion of noble metals easily damages the cells through the following reaction: …”
Section: Critical Issues In Plasmonic Photovoltaicsmentioning
confidence: 99%
“…(2) In any case, where thermal treatment is involved in the fabrication process, noble metal nanostructures are likely to lose their optical properties due to deformation, agglomeration, or Ostwald ripening. For example, high-temperature annealing (∼500 °C) is necessary to fabricate DSSCs, and plasmonic metal nanostructures coated with SiO 2 or TiO 2 layers kept their shape after the annealing process, indicating that protective layers can provide thermal and structural stability. , (3) In conventional DSSCs where iodine-based liquid redox couple is used, rapid corrosion of noble metals easily damages the cells through the following reaction: …”
Section: Critical Issues In Plasmonic Photovoltaicsmentioning
confidence: 99%
“…The nanograting patterns on the photoactive layer caused an increase in the EQE in the entire wavelength region (especially in the long-wavelength region) owing to the surface plasmon resonance (SPR) effect between the patterned photoactive layer and the metal electrode [19]. Similarly, the SPR effect was exhibited in the ultra-flexible device without nanograting patterns owing to the morphological characteristics of the Ag NWs [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The material properties of AgNWs provided excellent electronic conductivity of the photoanode, and the unique LSPR effect of nanometals significantly improved the light capture, which was the reason for the increased JSC. Huang et al [21] reported that the improved efficiency of DSSC made by AgNWs@TiO2 is due to the decrease of the interface charge transfer resistance and the ion diffusion resistance in the electrolyte. It is worth noting that with the increase of nanometal, one-dimensional nanostructures (AgNWs) are overloaded, and the host (TiO2) is not able to maintain the electron path.…”
Section: Measurements and Characterizationmentioning
confidence: 99%